Поселение «Усадьба Литвиненко» на Днепровском лимане - Былкова, В.П. (Материалы по археологии, истории и этнографии Таврии, 1996)
Litvinenko I Settlement is one of the monuments of Olbia agricultural district. The published materials are dated back to the end of the 5th - the first third of the 3d centuries B.C.